ANALYSIS OF THE SERVICE QUALITY TO CUSTOMERS AT NELAYAN RESTAURANT OF THE BELMOND JIMBARAN PURI BALI HOTEL - Ni Wayan Trisnayanti; I Ketut Suarja; Dewa Made Suria Antara; Ni Gusti Nyoman Suci Murni (Politeknik Negeri Bali, 2018)
The purpose of this research is to determine the service quality to customers and determine the indicators that need to be improved and maintained in the quality of services provided to customers at Nelayan Restaurant of the Belmond JimbaranPuri Bali. This research uses five variables: Tangibles (X1), Reliability (X2), Responsiveness (X3) Assurance (X4), and Empathy (X5) by using 14 indicators/questions. The type of data used in this research is the qualitative and quantitative data with proportionate stratified random sampling. The number of samples obtained 80 respondents. Data were analyzed by using the technique of importance-performance analysis. Collection of data through distributing questionnaires to the customers. The results show that more indicators are getting positive values than negative values, and there are several indicators that need to be improved, namely the indicator of employees are ready to provide assistance needed by guests (X3.1), employees are polite in serving guests (X4.1), and employees have acted for the benefit of guests (X5.1) as well as the indicators that need to be maintained such as the indicator of restaurant cleanliness (X1.1), condition of restaurant (X1.2), Food ingredients used in the restaurant (X1.3), Appearance of the restaurant employees (X1.4), and employees provide fast and precise services (X2.2).